Peppermint Essential Oil for Nausea and Vomiting in Hospitalized Patients: Incorporating Holistic Patient Decision Making Into the Research Design. (June 2021) - Mohr, Carla; Jensen, Cassandra; Padden, Nicole; Besel, Jamie M.; Brant, Jeannine M.
Aims: This study examined nausea and vomiting (N/V) in hospitalized patients following the use of inhaled peppermint essential oil (aromatherapy) compared to combined aromatherapy/antiemetics or antiemetics alone. Method and Materials: A total of 103 hospitalized patients were offered one of three options to control N/V. Patient choice was considered in the holistic trial design so that patients were not denied either the essential oil or antiemetics. Patients rated nausea 0 to 10 on the Edmonton Symptom Assessment Scale at symptom onset and within 60 minutes of the intervention. Results: Only three subjects enrolled in the antiemetic arm; thus this arm was eliminated from analysis, resulting in 100 evaluable patients. Mean nausea score improved significantly for the entire sample following the aromatherapy or aromatherapy/antiemetic intervention ( p < .0001). Patients in the aromatherapy arm had significant improvement in nausea compared to the combined aromatherapy/antiemetic arm ( p < .0001). Patient perception that peppermint oil relieves N/V significantly improved for the entire sample. Notable is that 65% of patients used peppermint essential oil alone. Conclusions: Peppermint essential oil is an effective independent or complementary modality for relief of N/V in hospitalized patients. Research designs that incorporate patient decision making should be considered for studies in which placebos do not contribute to holistic care.